Dietary polyunsaturated fatty acids and adaptation to chronic hypoxia alter acyl composition of serum and heart lipids - Balková, Patricie; Jezková, Jana; Hlavácková, Markéta; Neckár, Jan; Stanková, Barbora; Kolár, Frantisek; Novák, Frantisek; Nováková, Olga (The British journal of nutrition, 2009)
The effects of dietary supplementation with fat of different fatty acid profile and chronic intermittent hypoxia (CIH) on the fatty acid composition of serum and heart lipids were analysed. Adult male Wistar rats were fed a standard non-fat diet enriched with 10 % of lard, fish oil (n-3 PUFA) or maize oil (n-6 PUFA) for 10 weeks. After 4 weeks on the diets, each group was divided in two subgroups, either exposed to CIH in a barochamber (7000 m, twenty-five exposures) or kept at normoxia. In normoxic rats, the fish oil diet increased the level of conjugated dienes. The n-6:n-3 PUFA ratio in serum TAG, phospholipids (PL), cholesteryl esters (CE) and heart TAG, PL and diacylglycerols (DAG) followed the ratio in the fed diet (in the sequence maize oil>lard>fish oil). In heart TAG, PL and DAG, 20 : 4n-6 and 18 : 2n-6 were replaced by 22 : 6n-3 in the fish oil group. The main fatty acid in CE was 20 : 4n-6 in the lard and maize oil groups whereas in the fish oil group, half of 20 : 4n-6 was replaced by 20 : 5n-3. CIH further increased 20 : 5n-3 in CE in the fish oil group. CIH decreased the n-6:n-3 PUFA ratio in serum CE, heart TAG, PL and DAG in all dietary groups and stimulated the activity of catalase in the maize and fish oil groups. In conclusion, PUFA diets and CIH, both interventions considered to be cardioprotective, distinctly modified the fatty acid profile in serum and heart lipids with specific effects on conjugated diene production and catalase activity.
Keywords: Male; Rats, Wistar; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Adaptation, Physiological; chronická nemoc; kukuřičný olej; Hypoxia; Myocardium; omega-3 mastné kyseliny; mužské pohlaví; Dietary Fats; potkani Wistar; fyziologická adaptace; Chronic Disease; Corn Oil; Catalase; krysa rodu Rattus; rybí oleje; kyseliny mastné omega-6; dietní tuky; Cardiotonic Agents; lipidy; Animals; Fatty Acids, Unsaturated; Fish Oils; zvířata; katalasa; Rats; kardiotonika; Dietary Fats, Unsaturated; dietní tuky nenasycené; peroxidace lipidů; Lipids; Lipid Peroxidation; nenasycené mastné kyseliny; hypoxie; myokard